Optimalisasi Proses Administrasi, Produksi, dan Pemasaran pada UMKM Kerajinan Rotan Dayani Indonesia - Ningrum, Natalia Ratna; Farhan, Fikri; Indriati, Inayat Hanum; Zalzalah, Guruh Gifar; Susilowati, Fitri; Abdullah, Fadhil Ali (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service program aims to evaluate the application of operational management systems in the management of a rattan handicraft business. The activities carried out covered administrative and marketing aspects, including the updating of physical and digital product catalogs, warehouse reorganization, development of operational standard operating procedures (SOPs), preparation of financial reports, and creation of social media marketing content. The main results indicate improved operational efficiency at Dayani Indonesia and strengthened digital marketing strategies. The updated product catalog was successfully prepared and uploaded to online platforms, the warehouse layout became more organized through the implementation of a new shelf numbering system, and prototypes of wooden and bamboo woven products were successfully produced. Based on these outcomes, it can be concluded that the application of operational management principles effectively enhances the operational performance of the rattan handicraft MSME at Dayani Indonesia, supporting its development as a growing small enterprise.